Does Parental Disability Matter to Child Education? Evidence from Vietnam - Cuong, Nguyen Viet; Mont, Daniel (2012)
This paper examines the effect of parental disability on school enrollment and educational performance for children in the 2006 Vietnam Household Living Standards Survey. Results from instrumental-variables regressions indicate that children of parents with a disability have a lower enrollment rate in primary and secondary school of about 8 percentage points: 73 percent compared with 81 percent. However, the association of parental disability with educational performance is small and not statistically significant. The conclusion of the paper is that to achieve the Millennium Development Goal of universal primary school as well as increased coverage of secondary education, the government should have policies and programs that either directly support the education of children with disabled parents and/or have policies that support disabled adults, thus lessening the incentive for their children not to attend school.